Mathematical modeling of processes of radiolysis of water, hexane and water–hexane mixture - Agayev, T.N. (Вопросы атомной науки и техники, 2013)
There were carried out modeling of radiolysis processes in the water–hexane system for the purpose of to identify the mechanism of radiolysis and comparison of theoretical and experimental data. Проведено математическое моделирование процессов радиолиза воды, гексана и смеси вода–гексан с целью выявления механизма радиолиза и сравнение теоретических данных с экспериментальными. Проведено математичне моделювання процесів радіолізу, води, гексану та суміші вода–гексан з метою виявлення механізму радіолізу та порівняння теоретичних даних з експериментальними.